The decree of the Russian Federation Supreme Court Plenum of March 12, 2002, № 5 On the judicial practice for cases of stealage, exaction, and unlawful circulation of weapons, ammunition, explosives and explosive assemblies with the account of alterations and additions: the realized and the unimplemented - I. I. Bikeyev (Russian Journal of Economics and Law)
The article justifies the statement of regarding the decrees of the Russian Supreme Courts Plenums as voluntary but supported by the right of the mentioned bodies to abolish the inferior courts' decisions. The author analyzes the imperfections of the decree of the Russian Federation Supreme Court Plenum of March 12, 2002, № 5 and suggests amendments to them.